2015
DOI: 10.4081/jlimnol.2015.1338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water chemistry on zooplanktonic and microbial communities across freshwater ecotones in different macrophyte-dominated shallow lakes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Under these heterogeneity stream ecosystems, physicochemical-factor provides a diverse environment for bacterial communities [52,57], and DOC, NO 3 − , SRP, and TP provide available nutrients for bacterial growth [40,58]. Nutrients predominately explained the variation in lake bacterial communities, possibly due to the relatively uniform physical conditions [4,5]. Elevated inputs of phosphorus and nitrogen from its inflow streams have caused severe eutrophication and associated algae blooms in Erhai Lake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these heterogeneity stream ecosystems, physicochemical-factor provides a diverse environment for bacterial communities [52,57], and DOC, NO 3 − , SRP, and TP provide available nutrients for bacterial growth [40,58]. Nutrients predominately explained the variation in lake bacterial communities, possibly due to the relatively uniform physical conditions [4,5]. Elevated inputs of phosphorus and nitrogen from its inflow streams have caused severe eutrophication and associated algae blooms in Erhai Lake.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial assemblages are fundamental components of aquatic ecosystems and play a key role in biogeochemical cycles in both lotic and lentic ecosystems [1,2]. Their high diversity, small size, and rapid generation have caused microbes to become the most sensitive aquatic organisms to environmental perturbations, especially to nutrient alteration [3][4][5]. Understanding these responses is increasingly important given that biogeochemical cycles have been dramatically altered by human activities [6], with a two-fold increase in nitrogen (N) availability [7,8] and approximately a four-fold increase in phosphorus (P) mobilization [9,10] relative to preindustrial times.…”
Section: Introductionmentioning
confidence: 99%
“…is the most natural (forest catchment; peatbog bordering the lake to the south) and the deepest, dimictic, eutrophic water body with brown-coloured water. The structure of the macrophyte communities in the lakes were described by Sender (2012Sender ( , 2016 and Mieczan et al (2016). The highest phytolittoral zone occurs in Lake Skomielno, where 15 plant assemblages is represented by 55 species, and common reed comprises ca.…”
Section: Study Areamentioning
confidence: 98%
“…In eutrophic shallow lakes, periphytic assemblages have been shown to be associated with P tot and N tot (Jones and Sayer, 2003), and with a combination of physical variables, e.g. water level, and chemical variables, such as pH, N, and DOC (Mieczan et al, 2016). The RDA showed that nutrients were the dominant factors controlling distribution patterns in ciliate assemblages.…”
Section: Food Web Vs Environmental Parametersmentioning
confidence: 99%
“…Filamentous algae, even cyanobacteria, can be selectively consumed by macroinvertebrate grazers, such as the chironomid Endochironomus albipennis. Selective foraging on filamentous algae may significantly reduce their biomass (Tarkowska-Kukuryk, 2013;Mieczan et al, 2016). Temperature is another factor likely to substantially influence periphyton succession.…”
Section: Food Web Vs Environmental Parametersmentioning
confidence: 99%